1995
DOI: 10.1002/path.1711770207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the c‐kit gene product in normal and neoplastic mast cells but not in neoplastic basophil/mast cell precursors from chronic myelogenous leukaemia

Abstract: The expression of the c-kit gene product has been examined in normal mast cells, mast cell neoplasms, and basophil/mast cell precursors obtained from patients with chronic myelogenous leukaemia (CML). Formalin-fixed, paraffin-embedded sections or smears fixed with formalin vapour were studied by immunohistochemical methods, using a polyclonal antibody against the c-kit gene product. Normal and neoplastic mast cells showed a positive immunoreaction for c-kit gene product, but neoplastic basophil/mast cell precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…12 c-KIT expression is down-regulated during cell differentiation with the exception of mast cells that retain a high level of expression. 13 c-KIT is also expressed in melanocytes, testis, brain, vascular endothelial cells, interstitial cells of Cajal, breast glandular epithelial cells, and sweat glands. Remarkably, mutated forms of c-KIT were identified in tumors arising from most of these cell types.…”
Section: Physiologic Functionsmentioning
confidence: 99%
“…12 c-KIT expression is down-regulated during cell differentiation with the exception of mast cells that retain a high level of expression. 13 c-KIT is also expressed in melanocytes, testis, brain, vascular endothelial cells, interstitial cells of Cajal, breast glandular epithelial cells, and sweat glands. Remarkably, mutated forms of c-KIT were identified in tumors arising from most of these cell types.…”
Section: Physiologic Functionsmentioning
confidence: 99%
“…[17][18][19] Notably, in patients with CML, immature "basophillike" cells were found to react with antitryptase monoclonal antibody. 19 However, it could not be clarified whether the labeled cells were indeed basophils or MC-lineage cells. Our immunoelectron microscopy experiments clearly show that tryptase is expressed in the granule compartment of basophils in patients with CML, MDS, and IMF.…”
Section: Interpretation Of Datamentioning
confidence: 99%
“…17,18 Moreover, it was found that in patients with chronic myeloid leukemia (CML), immature granulated cells with characteristics of basophils react with antibodies against tryptase. 19 However, it could not be clarified whether these cells are indeed basophils, belong to the MC lineage, or would represent an "intermediate cell. "…”
Section: Introductionmentioning
confidence: 99%
“…16). Neoplastic transformation has been established via mutation of c-kit gene, which results in ligand-independent activation of the receptor in a number of human tumors such as human mast cell tumors (17,18), chronic myelogenous leukemia (19), germ cell tumors (20), and gastrointestinal stromal tumors (GISTs; Refs. [21][22][23].…”
Section: Introductionmentioning
confidence: 99%